Influence of Antihypertensive Drugs on Left Ventricular Hypertrophy Regression in Hypertensive Patients - Gautam, Mani Prasad; Sedhain , Sabina; Gurung , Puran; Paudel , Sophiya; Kandel , Govinda; Khatiwada , Prakash (Journal of National Heart and Lung Society Nepal, 2023)
Background: Hypertension and its effect on heart in the form of left ventricular hypertrophy are the important predictors of heart failure. Hypertension treatment and left ventricular hypertrophy regression is crucial in the prevention of cardiovascular disease. However, the impact of antihypertensive treatment on left ventricular hypertrophy is less studied and which particular class of antihypertensive medicine is more effective is largely unexplored in our population. We designed this study to explore this issue in subjects taking treatment by evaluation initial and after six months echocardiography findings. Methods: One hundred fifty subjects aged 25-75 years, taking antihypertensive medicine were enrolled in the study. Along with basic demographic and epidemiological data, initial and after 6 months echocardiographic findings were analyzed for the presence of LV hypertrophy regression. Choice of medicine and necessary changes for the achievement of blood pressure targets were done on treating physician’s discretion.Results: Out of 150 subjects, data for 130 subjects were available for final analysis. Mean age was 54.4 years with standard deviation of 12.3 years. Apart from age, smoking, overweight and obesity, dyslipidemia, and diabetes were the important risk factors with a prevalence of 28%, 26%, 22% and 20% respectively. Although the decrease in rates of LV hypertrophy over the duration of 6 months were not significant in overall and in subjects treated with various antihypertensive medicines, the reductions in LV mass index (108.76+/-11.3 to 98.46+/-11.23) in overall and in different antihypertensives were significant (p